Optimalisasi APE sebagai Sarana Edukasi Siswa PAUD melalui Pemberdayaan Industri Warga Ciganitri - Rizka Rachmawati; Imtihan Hanom; Naura Sujana (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
ABSTRACT APE is educational toy used to support children’ activity that can optimize the development of children's brains, especially for early children. APE becomes media that is used as a daily necessity by teaching teams and also students. However, the current conditions of APE are slowly beginning to be replaced by gadgets that are more likely to have a negative impact on children's development. So it takes an appropriate technological innovation to design APEs that match the purpose of sensory and motor stimulation of early childhood so that their brains and physical continues to develop actively in performing day-to-day activities. Given that the area around Bojongsoang, Bandung has a lot of household industries working in the furniture sector, the team plans to take advantage of the home industry and consider ergonomics, materials, child-safe finishes, connectivity systems and so on. The results of this activity will produce APEs that match the standards of early childhood play activities.